Modeling Effectiveness of Gradual Increases in Source Level to Mitigate Effects of Sonar on Marine Mammals: - Benda-Beckmann, A.M. von; Wensveen, P.J.; Kvadsheim, P.H.; Lam, F.P.A.; Miller, P.J.O.; Tyack, P.L.; Ainslie, M.A. (2013)
Ramp-up or soft-start procedures (i.e., gradual increase in the source level) are used to mitigate the effect of sonar sound on marine mammals, although no one to date has tested whether ramp-up procedures are effective at reducing the effect of sound on marine mammals. We investigated the effectiveness of ramp-up procedures in reducing the area within which changes in hearing thresholds can occur. We modeled the level of sound killer whales (Orcinus orca) were exposed to from a generic sonar operation preceded by different ramp-up schemes. In our model, ramp-up procedures reduced the risk of killer whales receiving sounds of sufficient intensity to affect their hearing. The effectiveness of the ramp-up procedure depended strongly on the assumed response threshold and differed with ramp-up duration, although extending the duration of the ramp up beyond 5 min did not add much to its predicted mitigating effect. The main factors that limited effectiveness of ramp up in a typical antisubmarine warfare scenario were high source level, rapid moving sonar source, and long silences between consecutive sonar transmissions. Our exposure modeling approach can be used to evaluate and optimize mitigation procedures